Does Prior Civilian Trauma Moderate the Relationship Between Combat Trauma and Post-deployment Mental Health Symptoms? - George, Brianna A. (Journal of interpersonal violence, 2022)
In addition to combat trauma, childhood and adult non-military, interpersonal trauma exposures have been linked to a range of psychiatric symptoms (e.g., alcohol use problems, posttraumatic stress disorder [PTSD], depression symptoms) in veterans. However, few studies simultaneously explore the associations between these civilian and combat trauma types and mental health outcomes. Using a sample of combat-exposed veterans who were previously deployed to Iraq and Afghanistan (N = 302), this study sought to (a) understand the independent associations of civilian interpersonal trauma (i.e., childhood trauma and non-military adult trauma) and combat-related trauma with post-deployment alcohol use, PTSD symptoms, and depressive symptoms, respectively and (b) to examine the interactive effects of trauma type to test whether childhood and non-military adult trauma moderate the association of combat trauma with these outcomes. A path analytic framework was used to allow for the simultaneous prediction of these associations. In the final model non-military adult trauma and combat trauma were found to be significantly associated with PTSD symptoms and depression symptoms, but not average amount of drinks consumed per drinking day. Childhood trauma was not associated with any outcomes (i.e., PTSD symptoms, depression symptoms, average amount of drinks consumed per day). Only combat trauma was significantly associated with average amount of drinks consumed per day. Results underscore the importance of assessing multiple trauma types and considering trauma as a non-specific risk factor, as different trauma types may differentially predict various mental health outcomes other than PTSD. Further, results highlight the noteworthiness of considering co-occurring outcomes within the veteran community. Limitations, future directions, and implications of diversity are discussed.